Penerapan E-Crm Pada Sistem Informasi Penjualan Di Toko Jati Aisyah Furniture Prabumulih Menggunakan Metode Fast - Apriansyah, Yugi (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
A sales information system is a system that provides information services that can make it easier to create sales transaction data, product data and customer data. In this case, the Jati Aisyah Furniture Store was used as a place for research because the sales system is still manual so errors often occur. The aim of the research is to build a sales information system to help shop owners make sales so that they can develop and be better in the future. The method used by the author is the FAST method, the data collection method used is primary and secondary data, the software used is Windows 10 Home, Visual Studio Code, and Xampp as database storage media